Characterisation of High-Density Polyethylene (DiaPow HDPE HX R) Powder for Use in Additive Manufacturing - Fredrick M. Mwania; Jacobus van der Walt; Lorinda Wu; Wayne Koen; Maina Maringa (Journal of Engineering)
High-density polyethylene (HDPE) is largely processed using conventional manufacturing techniques. However, there is a need to investigate its processability when fabricated using additive manufacturing (AM) in an effort to use this polymer for high-end applications, such as the fabrication of human implants. In this regard, the current study investigated the intrinsic and extrinsic properties of HDPE powders (DiaPow HDPE HX R) from Diamond Plastics GmbH, to determine its feasibility of use in powder bed fusion (PBF). Powder characterisation was undertaken using a scanning electron microscope (SEM), melt flow index (MFI) testing, tapped density testing, differential scanning calorimetry (DSC), thermogravimetric analysis (TGA), Fourier-transform infrared (FTIR) spectroscopy, and hot-stage microscopy. The analysis revealed that this high-density polyethylene powder is suitable for processing using PBF based on the particle size distribution (PSD) (65–92 μm), flowability (Hausner ratio = 1.22 ± 0.02), melting point range (125.7–135.2 degrees Celsius), enthalpy of melting (170.51 J/g), and thermal stability (the materials starts to degrade at 350.0 degrees Celsius and completely degrades at 500.0 degrees Celsius). It also showed good coalescence behaviour. However, the narrow sintering window (7.9 degrees Celsius) of the material indicates possible challenges of shrinkage and curling during printing. The material was also found to have poor absorptive properties of infrared radiation at 10.6 μm, which might make sintering using CO2 lasers challenging.